Capsicum annuum L. var. Cornetto di Pontecorvo PDO: Polyphenolic profile and in vitro biological activities. (January 2018) - Di Sotto, Antonella; Vecchiato, Martina; Abete, Lorena; Toniolo, Chiara; Giusti, Anna Maria; Mannina, Luisa; Locatelli, Marcello; Nicoletti, Marcello; Di Giacomo, Silvia
Graphical abstract: Highlights: Studying the functional properties of Capsicum annuum L. var. Cornetto di Pontecorvo PDO. Results highlighted different in vitro biological activities in which polyphenols and carotenoids could be involved. Antimutagenic activity against oxidative mutagens and environmental pollutants. Peel and seeds as potential nutraceutical sources to recover for industrial purposes. Abstract: In present study, the potential functional properties of the ethanolic extracts from peel, pulp, edible part and seeds of Capsicum annuum L. var. Cornetto di Pontecorvo were studied. The antimutagenicity against environmental pollutants and oxidative mutagens, the digestive enzyme inhibition, and the antioxidant properties were evaluated in relation to phenolic content. All the samples produced antimutagenic effects against 1-nitropyrene, 2-aminoantracene and tert -butyl-hydroperoxide, and inhibited α-amylase, without affecting α-glucosidase. Also, radical scavenging effects, inhibition of ROS-mediated lipoperoxidation and chelating activity were highlighted. The peel and seed extracts were in general the most effective samples. The phytochemical analysis highlighted a high amount of polyphenols, with a very low carotenoid content. Among phenolics, rutin, gallic acid, carvacrol, chlorogenic acid, 4-OH benzoic acid, and traces of quercetin and epicatechin were determined. Present results highlight a functional role of this pepper ecotype and suggest a possible use of its derived products as food supplements.